2014
DOI: 10.1007/s00300-014-1567-x
|View full text |Cite
|
Sign up to set email alerts
|

Isolated faecal bacterial communities found for Weddell seals, Leptonychotes weddellii, at White Island, McMurdo Sound, Antarctica

Abstract: The microbial diversity of faecal communities co-existing with mega fauna is not well understood even though these faecal communities are critical for health and development. Additionally, the transfer of microbial taxa among host animals is little studied. Here, we used 16S sequences obtained from clone libraries to characterise the faecal microbiota of Weddell seals breeding in McMurdo Sound and at White Island, Antarctica. Faecal bacterial communities were dominated by four phyla; Actinobacteria (20 %), Bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 52 publications
3
9
0
Order By: Relevance
“…Our findings greatly expand upon observations describing the fecal microbiota of a single sea lion determined from feces collected from Seal Bay, Kangaroo Island, Australia, in which Firmicutes contributed ϳ80% to the microbial community composition (5,18,20). Similar fecal microbiota composition and Firmicutes dominance have been observed in other pinniped species, including Australian fur, leopard, southern elephant, and Weddell seals, suggesting that the Firmicutes are a core group within the pinniped microbiota.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Our findings greatly expand upon observations describing the fecal microbiota of a single sea lion determined from feces collected from Seal Bay, Kangaroo Island, Australia, in which Firmicutes contributed ϳ80% to the microbial community composition (5,18,20). Similar fecal microbiota composition and Firmicutes dominance have been observed in other pinniped species, including Australian fur, leopard, southern elephant, and Weddell seals, suggesting that the Firmicutes are a core group within the pinniped microbiota.…”
Section: Discussionsupporting
confidence: 79%
“…However, marine mammal samples used for studies and comparisons of microbiota have almost entirely come from seals of various species (5,(17)(18)(19)(20)(21). Such studies have found that the microbiota are largely dominated by four phyla, Firmic- …”
mentioning
confidence: 99%
“…et al, 2010), indicating their presence even in polar ecosystems. Proteobacteria have also previously been identified in the fecal microbiome (12.9% relative abundance) of this species (Banks et al, 2014), suggesting that gram-negative bacteria are an important part of their gut microbial community. A healthy gut barrier prevents the translocation of live bacteria into the tissues and circulation, a process that, if defective, would expose animals to acute infectious and inflammatory challenge, and could produce sepsis (Balzan et al, 2007;Schuijt et al, 2013).…”
Section: Relevance Of Lps Stimulation and Observed Responsesmentioning
confidence: 73%
“…; Banks et al . ). Cellulose‐utilizing bacterial populations were detected in the faeces of dugong, Dugong dugon (Tsukinowa et al .…”
Section: Introductionmentioning
confidence: 97%